2003
DOI: 10.1002/nau.10149
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the function of the female urethra: II: Relation between maximum urethral closure pressure at rest and the degree of urethral incompetence

Abstract: This study demonstrates that there is a highly significant relationship between MUCP and between all grades of urethral incompetence. This supports previous observations that MUCP decreases when abdominal leak point pressure (ALPP) is low and that this might be secondary to some mechanical failure in the pressure transmission from the abdominal cavity to the urethra. Studies should never compare continent to incontinent cohorts without considering their ALPP because in doing so they are comparing groups that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…MUCP also decreases with aggravation of urethral incompetence, i.e., decrease in CLPP [Schick et al, 2003b]. The degree of urethral incompetence is the clinical manifestation of faulty transmission of abdominal pressure to the proximal urethra.…”
Section: Discussion and Overviewmentioning
confidence: 98%
See 1 more Smart Citation
“…MUCP also decreases with aggravation of urethral incompetence, i.e., decrease in CLPP [Schick et al, 2003b]. The degree of urethral incompetence is the clinical manifestation of faulty transmission of abdominal pressure to the proximal urethra.…”
Section: Discussion and Overviewmentioning
confidence: 98%
“…In the second part of the study [Schick et al, 2003b], we analyzed the relationship between MUCP and the degree of urethral incompetence, which is synonymous with abdominal (cough) leak point pressure (CLPP). This study demonstrated that MUCP decreases signi¢cantly, parallel to the increase in urethral incompetence.…”
Section: Introductionmentioning
confidence: 99%